Construction and civil demolition in Espinosa, Minas Gerais: mapping of waste disposal places (Revista Espinhaço, 2018)
The impulse in the growth of any developed country, goes through the civil construction. Having the power to change the landscape, bringing economic and social benefits to the population, as well as helping to generate employment and quality of life. Environmental problems in the city of Espinosa / MG deserve to be studied, since solid waste from construction is not being used in a technical and conscious way. This research was based on bibliographic reviews, field visits, comparison of satellite images, photographs, technical reports from municipal agencies and interviews with authorities in the area. There were visits to irregular points of waste disposal, with the purpose of portraying in situ the disposition of the RCC. This work aims to map the points of disposal, to show how much the urbanization of the city has changed the landscape and causing environmental damage, and may be subsidies for government authorities in solving the problem.
Keywords: Construction Waste; Espinosa-MG; environment